Chapter 7. Evelyn Briggs Baldwin and Kersting Bay - Cruz, Alejandro (Septentrio Conference Series, 2015)
A letter from Evelyn Briggs Baldwin to the photographer Rudolf Kersting in May of 1898 lends credence to the notion that the two men were close associates, shared membership in the Arctic Club of America, and that Kersting was the personality behind Baldwin’s place name of Kersting Bay on Wilczek Island in Franz Josef Land later in 1898 during the second Wellman polar expedition.